Sustainability in Organizations: New approaches and ways of understanding the concept - Carrillo González, Graciela (Administración y Organizaciones, 2025)
The most significant antecedent of sustainability emerged with the emergence of environmental movements in the United States, which were catalyzed by Rachel Carson’s work "Silent Spring," published in 1962. In this seminal work, Carson exposed the extinction of birds (particularly the bald eagle) due to the excessive use of DDT in crops. Subsequently, in 1972, the United Nations Conference on the Human Environment was held in Stockholm, Sweden. During this conference, the impacts of the prevailing economic model were scrutinized, and discussions revolved around environmental protection and the exploration of common ground between environmental concerns and economic issues related to capital, growth, and employment. This early 1970s discourse engendered a stance that juxtaposed economic growth with environmental stewardship, giving rise, for the first time, to the proposition of zero growth.